Problemas de la acomodación, incidencia y progresión de la miopía en niños en edad escolar tras confinamiento por Covid-19 (2022)
This study aims to identify the main abnormalities related to accommodative problems and myopia progression in school-aged children aged 3- 18 years after Covid-19 confinement